Topical antiinflammatory activity of two pimarane diterpenes from Kaempferia pulchra - Ubonwan Pongprayoon (2018)
Two diterpenes, 2α-acetoxysandraracopimaradien-1α-ol (1) and sandaracopimaradien-1α,2α-diol (2) isolated from Kaempferia pulchra Ridl. (Zingiberaceae), have been assayed for topical antiinflammatory activity in the model of 12-O-tetradecanoylphorbol-13-acetate-induced ear oedema in rats. Both substances were found active and the ID50-values were estimated to be 330 and 50 μg/ear, respectively. The ID50-value of the reference drug diclofenac was calculated to 90 μg/ear.